Data Interoperability Model in Integrated Public Service Applications Based on Government Service Bus (Case Study: Tangerang Regency Communication and Information Office) - Fathan Ali, Dudy; Fatonah, Nenden Siti; Firmansyah, Gerry; Akbar, Habibullah (Jurnal Indonesia Sosial Sains, 2023)
The Tangerang Regency Government, as part of its digital transformation efforts, has been working to enhance public services through the development and implementation of e-Government initiatives. This research aims to conduct an in-depth analysis of data interoperability service modeling in e-Government applications based on Web Services using the Government Service Bus (GSB). The study will address the advantages and challenges associated with using the Government Service Bus, and provide practical recommendations for implementing the Government Service Bus as an effective application integration solution. COBIT 2019 is used as an assessment tool for the current condition. The research results reveal that a total of 138 applications have been identified, with 74 of them being public service applications. While 80% of the public service sector has been incorporated into integrated public service applications, their utilization remains limited. The current capability level of APO11 is at level 1, with an expected level of 2. Similarly, APO14 is at level 1, expected to reach level 2, and MEA01 is at level 0, with an expected level of 2. The author has proposed a data interoperability model that can be implemented within the Tangerang Regency Communication and Information Office, utilizing GSB as the middleware for interoperability processes, particularly for public service applications. Based on the proposed data interoperability model, the author also concludes that with its implementation, the Communication and Information Office will be able to address a significant portion of the technical recommendations derived from the gap analysis, although not necessarily all of them.